Transcription of a silkworm tRNA(cAla) gene is directed by two AT-rich upstream sequence elements. - Palida, F A (1993)
A region within 35 nucleotides upstream of the transcription initiation site of a variety of silkworm Class III templates is absolutely required for transcription in vitro. To determine whether the activity of this region can be attributed to a particular sequence element, we systematically replaced 4-5 bp segments of the region upstream of a silkworm tRNA(cAla) gene. We show that replacement of either of two AT-rich blocks markedly impairs promoter function, whereas replacement of other sequences has little or no effect. Additional mutants were constructed to test whether base composition or sequence is important for function of the AT blocks. We find that some sequences are more effective than others, but that various AT-rich sequences can direct transcription at a high level. Possible mechanisms by which such elements could act are discussed.